THE EFFECT OF HEALTH EDUCATION ON HANDLING OF VICTIMS' EVACUATION ON COMMUNITIES WITH INITIAL MEASURES OF TRAFFIC ACCIDENT - Lombogia, Moudy; Tambuwun, Semuel; Koapaha, Carensia Yulin Ingke (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2022)
Background: Traffic accidents are a public health problem that affects all sectors of life. accidents occur all the time and are for some age groups the single major cause of death. Evacuation is a process in which the placement of people from dangerous places to safer places to reduce health problems and the lives of vulnerable people. Methods: This study uses a literature review research type, which is a study in the form of a literature review using the results of previous research or textbooks or research journals. To obtain data in accordance with the topic, the researcher conducted a search for national and international-based journals on three databases, namely Google Scholar, Pubmed, Science Direct using the keywords health education, victim evacuation, traffic accidents. Results: there is an effect of health education on handling the evacuation of victims and the initial action of traffic accidents. Key words: health education, victim evacuation, community, knowledge, traffic accidents.